JURIDICAL PROBLEMS OF ACQUIRING PROPRIETARY RIGHTS TO STATE LAND THROUGH FULL SYSTEMATIC LAND REGISTRATION (PTSL) - Ni Made Jaya Senastri; Nengah Renaya; Arisya Septyani Virgin (Warmadewa Press, 2022)
This study aims to examine the weaknesses of obtaining property rights on state land and the legal consequences of the issuance of property rights on state land through a legally flawed Complete Systematic Land Registration (PTSL). The method used is a normative legal writing method, using a statutory approach, a conceptual approach, and a historical approach. As an analytical tool for the legal issues studied, this study uses the theory of legal certainty, the theory of legal protection and the theory of legal justice. Based on the results of the analysis, it can be found that there is an inconsistency of norms between the Minister of ATR/BPN Number 6 of 2018 and Government Regulation Number 24 of 1997, namely Article 33, Article 22 paragraph (2), Article 24 paragraph (2) of the Minister of ATR/BPN Regulation No. 6 of 2018. The existence of the inconsistency of these norms creates legal weaknesses and uncertainty in the community regarding the suspension of BPHTB and PPh debts, a statement of ownership of rights in good faith, the principle of publicity for the announcement of physical data and juridical data, the application of the principle of contradictory delimitation in determining the boundaries of land parcels through Complete Systematic Land Registration (PTSL). The result or output in the form of a certificate of ownership that is issued has a legal defect. The legal consequences of the issuance of a certificate of ownership of state land through a Complete Systematic Land Registration (PTSL) which is legally flawed, namely cancellation due to a defect in administrative law and cancellation by implementing a court decision that has permanent legal force.